Undernutrition and Associated Factors Among Adult Tuberculosis Patients in Jigjiga Public Health Facilities, Somali Region, East, Ethiopia - Muse, Abdilahi Ibrahim (Res Rep Trop Med, 2021)
BACKGROUND: Tuberculosis and undernutrition are the public health concerns of people living in middle and low-income countries. When patient develops TB, undernutrition is not only a risk factor for progression of latent TB infection to active disease, but also intensifies the risk of drug toxicity, relapse and death. Nutritional supplementation in patients with TB is associated with faster sputum conversion, higher cure and treatment completion rates, and body-weight gain. OBJECTIVE: To find out the magnitude of undernutrition and associated factors among adult tuberculosis patients in jigjiga public health facilities. METHODS AND MATERIALS: A facility-based cross-sectional study design was applied. Data were collected using a structured questionnaire while anthropometric measurements were collected in their scale measurements. The data were entered into an Epi-data version 3.1, then were exported and analyzed using SPSS v20. Bivariate logistic regression was done to assess the association between the outcome variable and the independent variables, value <0.25 was considered as a candidate for multivariate logistic regression at 95% CI. In multivariable logistic regression analysis, the level of statistical significance was declared at a p-value less than 0.05. RESULTS: The magnitude of undernutrition was 44.3% [95% CI (38.2, 49.7)]. Sex (female) [AOR=1.769, CI=1.035, 3.024], educational status [AOR=3.939, CI=2.285, 6.792] and being Bedridden [AOR=3.718, CI=1.115, 12.394) were predictors of Undernutrition among adult tuberculosis patients. CONCLUSION: The magnitude of undernutrition among adult patients with TB was high in the area. Overall routine appropriate nutrition assessment and support should be given to undernourished patients with TB. The level of education about nutrition should be improved by counseling on a balanced diet to all patients with TB and particularly for female patients. Appropriate nutrition support should be provided to undernourished TB patients, and more focused on those who are bedridden.